The effectiveness of Patient Controlled Analgesia (PCA) morphine-ketamine compared to Patient Controlled Analgesia (PCA) morphine to reduce total dose of morphine and Visual Analog Scale (VAS) in postoperative laparotomy surgery - Mahaalit Aribawa, I Gusti Ngurah; Agung Senapathi, Tjokorda Gde; Wiryana, Made; Sinardja, I Ketut; Budiarta, I Gede; Gede Widnyana, I Made; Aryabiantara, I Wayan; Parami, Pontisomaya; Nyoman Kurniasari, Pande; Putra Pradhana, Adinda (Bali Journal of Anesthesiology, 2017)
Background: Laparotomy may cause moderate to severe after surgery pain, thus adequate pain management is needed. The addition of ketamine in patient controlled analgesia (PCA) morphine after surgery can be the option. This study aims to evaluate the effectiveness of PCA morphine-ketamine compared to PCA morphine in patient postoperative laparotomy surgery to reduce total dose of morphine requirement and pain intensity evaluated with visual analog scale (VAS). Methods: This study was a double-blind RCT in 58 patients of ASA I and II, age 18-64 years, underwent an elective laparotomy at Sanglah General Hospital. Patients were divided into 2 groups. Group A, got addition of ketamine (1mg/ml) in PCA morphine (1mg/ml) and patients in group B received morphine (1mg/ml) by PCA. Prior to surgical incision both group were given a bolus ketamine 0,15mg/ kg and ketorolac 0,5mg/kg. The total dose of morphine and VAS were measured at 6, 12, and 24 hours postoperatively. Result: Total dose of morphine in the first 24 hours postoperatively at morphine-ketamine group (5,1Â±0,8mg) is lower than morphine only group (6,5Â±0,9mg) p<0,001. VAS (resting) 6 and 12 hour postoperative in morphine-ketamine group (13,4Â±4,8 mm) and (10,7Â±2,6 mm) are lower than morphine (17,9Â±4,1mm) pâ¤0,05 and (12,8Â±5,3mm) pâ¤0,05. VAS (moving) 6, 12, and 24 hour postoperative morphineketamine group (24,8Â±5,1mm), (18Â±5,6mm) and (9Â±5,6mm) are lower than morphine (28,7Â±5,2mm) pâ¤0,05, (23,1Â±6,0mm) pâ¤0,05, and (12,8Â±5,3mm) pâ¤0,05. Conclusions: Addition of ketamine in PCA morphine for postoperative laparotomy surgery reduces total morphine requirements in 24 hours compared to PCA morphine alone.